Epidemiological and Clinical Characteristics of Respiratory Syncytial Virus Infections in Children Aged <5 Years in China, from 2014–2018 - Hangjie Zhang; Aiqing Zhu; George F. Gao; Zhongjie Li (Vaccines, 2022)
Respiratory syncytial virus (RSV) is an important pathogen that causes acute respiratory tract infections in children. To understand the epidemiological and clinical characteristics of RSV in children, we analyzed the RSV diagnostic testing results from the 2014–2018 surveillance of acute respiratory infections in China. Among children aged <5 years, RSV incidence during 2014–2018 was 17.3% (3449/19,898), and 89.1% of RSV-positive individuals were inpatients. Children aged < 6 months had a high proportion in RSV infected individual (n = 1234; 35.8%). The highest RSV detection rate was in winter, RSV-A and RSV-B co-circulated year-round and jointly prevailed in 2015–2016. Cough was the common symptom of RSV infection 93.2% (3216/3449). Compared with older children, those aged <6 months were more likely to show breathing difficulty or lung rale that further developed into bronchopneumonia (p < 0.001). The symptoms such as cough, running nose, and diarrhea had significant differences between the RSV-A and RSV-B groups. The rate of RSV co-detection with other viruses or bacteria was 35.4%. Those coinfected with other viruses had a significantly higher incidence of fever, whereas those coinfected with bacteria had higher incidences of breathing difficulty and severe pneumonia. Our findings highlight the need for accumulating epidemiological information for the prevention and control of RSV.